2018
DOI: 10.5152/iao.2018.4690
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline versus Steroid Therapy for Idiopathic Sudden Sensorineural Hearing Loss with Diabetes

Abstract: OBJECTIVES:To compare the efficacy of pentoxifylline with that of conventional steroid therapy in diabetic patients with idiopathic sudden sensorineural hearing loss (ISSNHL) and to compare blood sugar levels during hospitalization. MATERIALS and METHODS:Medical charts were retrospectively reviewed for all diabetic patients admitted to one institution for ISSNHL between 2000 and 2015. We analyzed 298 cases; 50 patients received pulse steroid treatment (steroid group) and 248 received intravenous administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Sudden deafness is a sudden onset of sensorineural hearing loss manifested as unilateral hearing loss, which can be accompanied by tinnitus, ear blockage, dizziness, nausea, and vomiting. It usually occurs suddenly within 72 hours, and the hearing loss of two adjacent frequencies can be found to be greater than or equal to 20 dBHL during pure tone audiometry [ 22 ]. The causes of sudden deafness are more complicated and may be related to factors such as inner ear blood supply disorder and viral infection [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sudden deafness is a sudden onset of sensorineural hearing loss manifested as unilateral hearing loss, which can be accompanied by tinnitus, ear blockage, dizziness, nausea, and vomiting. It usually occurs suddenly within 72 hours, and the hearing loss of two adjacent frequencies can be found to be greater than or equal to 20 dBHL during pure tone audiometry [ 22 ]. The causes of sudden deafness are more complicated and may be related to factors such as inner ear blood supply disorder and viral infection [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral or IV applied systemic steroids are standard recommended eff ective treatment modality, and also the most frequently used management of SSNHL. 10,11 Lan et al…”
Section: Discussionmentioning
confidence: 99%
“…found that systemic corticosteroid therapy were not superior to Pentoxifylline treatment for the management of SSNHL in patients with Diabetes Mellitus. 10 We preferred to apply IV systemic corticotherapy (prednisolone) to all our patients because all of the patients were hospitalized and had vascular access. Corticosteroids also can be given to SSNHL patients as local application via intratympanic injection primarily or as a salvage management successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Pentoxifylline is a hemorheologically active phosphodiesterase inhibitor that is a treatment option for sudden sensorineural hearing loss [8][9][10]. Recent data also suggest that pentoxifylline protects the inner ear from amikacin-induced ototoxicity [11].…”
Section: Introductionmentioning
confidence: 99%